Security : dialogue across disciplines - Bourbeau, Philippe, 1972 November 3- (Cambridge : Cambridge University Press, 2015)
Security is a vital subject of study in the twenty-first century and a central theme in many social science disciplines. This volume provides a comparative analysis of the ways in which the concept of security is theorized and studied across different disciplines. The book has two objectives: first, to explore the growing diversity of theories, paradigms, and methods developed to study security; and, second, to initiate a multidisciplinary dialogue about the ontological, epistemological, paradigmatic, and normative aspects of security studies in social sciences. Readers across nine fields are invited to reflect on their conceptualizations of security and to consider how an interdisciplinary dialogue can stimulate and enrich the understanding of security in our contemporary world. Analytically sharp yet easy to read, this is a cutting-edge volume exploring what security is and what it means in today's world.
A multidisciplinary dialogue on security / Philippe Bourbeau -- Philosophy : The concepts of security, fear, liberty, and the state / Jonathan Herington -- Anthropology/ies : Moving beyond disciplinary approaches to security / Daniel M. Goldstein -- Geography : Securing places and spaces of securitization / Philippe Le Billon -- Sociology : Security and insecurities / Lisa Stampnitzky and Greggor Mattson -- International relations: Celebrating eclectic dynamism in security studies / Philippe Bourdeau, Thierry Balzacq, and Myriam Dunn Cavelty -- Psychology : The phenomenology of human security / Thomas C. O'Brien and Linda R. Tropp -- International political economy: Conceptual affinities and substantive differences with security studies / Romen Palan and Hannah Petersen
Title from publisher's bibliographic system (viewed on 10 Dec 2015).
Keywords: Security, International; National security; Internal security; Human security; Economic security